CD19 LYMPHOCYTE PROLIFERATION INDUCED BY Bifidobacterium animalis subsp. lactis IN C57BL/6 MICE EXPERIMENTALLY INFECTED WITH Toxoplasma gondii - RIBEIRO, Claudia de Mello; ZORGI, Nahiara Esteves; MEIRELES, Luciana Regina; GARCIA, João Luis; ANDRADE JUNIOR, Heitor Franco de (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Toxoplasmosis is frequently acquired through the oral route by the ingestion of cysts or oocysts of Toxoplasma gondii. Once ingested, the parasites penetrate the intestinal epithelial cells and rapidly disseminate to all organs in the host. During T. gondii infection, the intestinal microbiota plays an important role in stimulating a protective immune response against the parasite. In this sense the use of probiotics is worthy of note since they are live microorganisms that have beneficial effects on the host through stimulation of the immune response that can be important in the control of T. gondii proliferation and dissemination in the host. In the present study, the action of the probiotic Bifidobacterium animalis subsp. lactis was investigated in C57BL/6 mice infected with oocysts of ME49 strain of T. gondii. The probiotic had an immunomodulatory action, inducing CD19 lymphocyte proliferation and consequently increasing anti-T. gondii antibody level.Bifidobacterium animalis subsp. lactisprovided protection in supplemented mice, compared to the control group. In addition, supplemented animals had milder inflammatory process in the small intestine, indicating that the probiotic protects the intestinal mucosa during infection with T. gondii. It was concluded that the probioticB. animalis subsp. lactis induces humoral immune response capable of providing protection against T. gondii infection.